Bacillus amyloliquefaciens YN201732 Produces Lipopeptides With Promising Biocontrol Activity Against Fungal Pathogen Erysiphe cichoracearum - Jiao, Rong; Cai, Yongzhan; He, Pengfei; Munir, Shahzad; Li, Xingyu; Wu, Yixin; Wang, Junwei; Xia, Mengyuan; He, Pengbo; Wang, Ge; Yang, Huanwen; Karunarathna, Samantha C.; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Bacillus amyloliquefaciens YN201732 is an endophytic bacteria with high biocontrol efficiency and broad-spectrum antimicrobial activities. In order to clarify the main active ingredients and their antifungal mechanisms against powdery mildew of tobacco, this study is focused on lipopeptide obtained through acid precipitation and organic solvent extraction. HPLC and LCMS-IT-TOF were used to separate and identify antimicrobial lipopeptides. Findings revealed that bacillomycin D plays an important role against surrogate fungal pathogen Fusarium solani. Synthetic pathways of sfp, bacillomycin D, and fengycin were separately disrupted. The sfp gene knockout mutant B. amyloliquefaciens YN201732M1 only showed minor antagonistic activity against F. solani. While Erysiphe cichoracearum spore germination was inhibited and pot experiments displayed a significant decrease in tobacco powdery mildew. The spore inhibition rate of YN201732M1 was only 30.29%, and the pot experiment control effect was less than 37.39%, which was significantly lower than that of the wild type. The inhibitory effect of mutant YN201732M2 (deficient in the production of bacillomycin D) and mutant YN201732M3 (deficient in the production of fengycin) on the spore germination of E. cichoracearum were 50.22% and 53.06%, respectively, suggesting that both fengycin and bacillomycin D had potential effects on spore germination of powdery mildew. Interestingly, in a greenhouse assay, both B. amyloliquefaciens YN201732M2 and YN201732M3 mutants displayed less of a control effect on tobacco powdery mildew than wild type. The results from in vitro, spore germination, and greenhouse-pot studies demonstrated that antimicrobial lipopeptides especially bacillomycin D and fengycin may contribute to the prevention and control of tobacco powdery mildew. In addition, gene mutation related to lipopeptide synthesis can also affect the biofilm formation of strains.